Teologi Pendidikan Multikultural - Suripto (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2017)
The declining awareness of the diversity of values and the strengthening of the recent egocentrism of the group has disturbed the attention of many and worried about the joints of the life of society, nation and state. To be presented a religion is essentially a multicultural paradigmatic answer to all universal human problems regardless of race, gender, ethnicity, culture, language, and so on. What is the formulation of cooperation between religious and inter-religious people in an effort to achieve a peaceful, tolerant, co-operative, peaceful, coexistent, and exemplary society? To answer that question seems to require a religious understanding based on inclusive, humanist and multicultural theology. The presence of multicultural education theology is expected to contribute to solving the above problems.